Adult Hippocampal Neurogenesis Can Be Enhanced by Cold Challenge Independently From Beigeing Effects - Kim, Jong Whi; Han, Kyu Ri; Kim, Woosuk; Jung, Hyo Young; Nam, Sung Min; Yoo, Dae Young; Hwang, In Koo; Seong, Je Kyung; Yoon, Yeo Sung (Frontiers in Neuroscience, 2019)
In this study, we investigated the effects of cold challenge on adult hippocampal neurogenesis (AHN) and hippocampal gene expression and whether these are mediated by beigeing of peripheral fat tissues. Cold challenge (6 ± 2°C) for 1 and 4 weeks was found to induce beigeing effects in inguinal white adipose tissue based on hematoxylin and eosin staining as well as uncoupled protein-1 immunohistochemical staining. In the hippocampus, cold challenge for 1 or 4 weeks increased dentate gyrus neurogenesis and expression of genes related to AHN, including notch signaling, G protein-coupled receptor signaling, and adrenergic beta receptor-1. However, this enhancement of neurogenesis and gene expression by cold challenge was not shown by administration of CL 316,243, which induces peripheral beigeing similar to cold challenge but does not cross the blood-brain barrier. These results suggest that cold challenge promotes AHN and central expression of AHN-related, signaling, and β1-adrenergic receptors genes, and that peripheral beigeing by itself is not sufficient to mediate these effects. Considering the increase in AHN and gene expression changes, cold challenge may offer a novel approach to hippocampal modulation.